PENGARUH. BIAYA A PRODUKSI DAN OPERASIONAL TERHADAP LABA BERSIH PERUSAHAAN SEKTOR INDUSTRI BARANG DAN KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2018-2020 - Rizal Indra Tjahya; Farhani Nurfitri (Institut Bisnis Muhammadiyah Bekasi, 2022)
This research aims to find out how much effect production costs and operating costs have on the net income of manufacturing companies. This research uses a sample of companies engaged in the consumer goods industry sector listed on the Indonesia Stock Exchange. A sample of companies used as many as 18 companies from a total population of 60 companies. This type of research uses quantitative methods. The data used in this study is secondary data in the form of company financial statements obtained from www.idx.co.id website. The study used analytical methods with the help of SPSS Version 25. The results showed that production cost partially had a significant effect on net income. Operating expenses partially affect net income. Simultaneously, production cost and operating cost affect net income in consumer goods industry companies listed on the Indonesia Stock Exchange for 2018-2020.